2011
DOI: 10.1002/dev.21004
|View full text |Cite
|
Sign up to set email alerts
|

To have and to hold: Episodic memory in 3‐ and 4‐year‐old children

Abstract: Episodic memory endows us with the ability to reflect on our past and plan for our future. Most theorists argue that episodic memory emerges during the preschool period and that its emergence might herald the end of childhood amnesia. Here, we show that both 3- and 4-year-old children form episodic memories, but that 3-year-old children fail to retain those memories following a delay (Experiments 1 and 2). In contrast, 4-year-old children retained episodic memories over delays of 24 hr (Experiment 1) and 1 wee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
100
2
4

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(119 citation statements)
references
References 58 publications
13
100
2
4
Order By: Relevance
“…However, distinct neural networks and activation patterns have also been proposed for episodic and working memory processing, and in this paper we will describe how these are organized in the typically developing brain. At a behavioural level, the capacity to form episodic memories is believed to emerge at around 4 to 5 years of age,4 and episodic memory performance improves during childhood until adolescence, with older children being more successful at integrating information with its contextual details 5. Such improvements may parallel the development of the brain's connectional architecture, which we describe in detail later in this review.…”
mentioning
confidence: 96%
“…However, distinct neural networks and activation patterns have also been proposed for episodic and working memory processing, and in this paper we will describe how these are organized in the typically developing brain. At a behavioural level, the capacity to form episodic memories is believed to emerge at around 4 to 5 years of age,4 and episodic memory performance improves during childhood until adolescence, with older children being more successful at integrating information with its contextual details 5. Such improvements may parallel the development of the brain's connectional architecture, which we describe in detail later in this review.…”
mentioning
confidence: 96%
“…In the first place, the age at which performance on video selection rose above chance in the jungle task is not markedly different from the age at which children succeed on other "conceptual" (see Introduction) tests of episodic memory using free recall (Perner and Ruffman, 1995), direct-versus-indirect experience , and the spoon-test methodology (Scarf et al, 2013). It is likely, then, that requiring children explicitly to represent themselves in the past in an episodic memory task makes no significant cognitive demands additional to those recruited by these other conceptual episodic tasks.…”
Section: The Significance Of Success After Four-and-a-half Yearsmentioning
confidence: 93%
“…That both episodic memory and episodic foresight develop in tandem is consistent with neuroscientific evidence demonstrating that both of these processes rely on the activation of many of the same neural regions (e.g., Addis, Pan, Vu, Laiser, & Schacter, 2009). Scarf et al (2013) also examined episodic memory for the problem and used a delay between problem presentation and item selection. They showed that despite being able to form episodic memories for the problem, when the delay between the Development of Memory Futures 7 problem and solution selection was longer than 15 minutes, 3-year-olds did not retain the relevant problem information over the delay.…”
Section: Development Of Memory Futuresmentioning
confidence: 99%
“…Indeed, these findings are in line with a wealth of evidence showing that improvement in children's ability to store information in memory (i.e., consolidation) is critical to the development of episodic memory (Bauer, 2009). What Scarf et al (2013) have added is that these changes in retention of past experiences are also critical to the development of episodic foresight.…”
Section: Development Of Memory Futuresmentioning
confidence: 99%
See 1 more Smart Citation